Algerian-Ottoman military cooperation (1792-1830) (Journal of the College of Education for Women, 2019)
Facts and information contained in the search show that Algerian Ottoman military cooperation began since correlation Algeria with the Ottoman Empire in 1518, which was achieved after the Ottoman sultan response to the request of Algerians; there was a remarkable collaboration, according to the available capacity, and according to their needs.A manifestation of this cooperation can be seen land and sea army, which represented in the entry of the first squad of Janissary army to Algeria in 1519, and the formation of the Algerian fleet, which was an important force in Arab side of Mediterranean sea, but it loses its independent leadership when it reaches Istanbul and becomes part of the Ottoman fleet.Also, military buildings represented with forts and towers and trenches are considered another kind of military cooperation, as well as military aid with weapons which had appositive impact on the defensive device of Algeria in this difficult period. Armies expenses as they represent the military cooperation between Algeria and the Ottoman Empire, as well as cooperation in many battles and war that face both.